Pengaruh Label Halal, Kesadaran Halal, Dan Iklan Terhadap Keputusan Pembelian Pada Produk Sour Sally Di Indonesia - Hutami, Rizqiah Ade; Artadita, Sherly (eProceedings of Management, 2024)
This study aims to analyze the influence of Halal Label, Halal Awareness, and advertising on the purchase decisionof Sour Sally products in Indonesia. The method used was quantitative with descriptive analysis and multiple linearregression. The research population is Indonesian Muslims who have bought Sour Sally. The sampling technique usedwas nonprobability sampling with purposive sampling, involving 203 respondents and using an ordinal scale.Descriptive results showed that Halal Labels were rated very good (86%), Halal Awareness was very good (91%),advertising was good (81%), and purchase decisions were very good (84%). Partially, Halal Label, Halal Awareness,and advertising each have a positive and significant effect on purchasing decisions. Simultaneously, these threevariables also have a positive and significant effect on purchase decisions..Keywords-halal label , halal awareness, advertising, purchasing decision